Study of Mechanical Properties of Composite Material Based on Polypropylene and Vietnamese Rice Husk Filler - Thanh Duy Tran; Mao Dang Nguyen; C. N. Ha Thuc; H. Ha Thuc; Tai Dang Tan (Journal of Chemistry)
Nowadays, the consideration of the environmental impact of polymer products has led to the development of new materials combining polymers and renewable resources. Among these materials, biocomposites have been extensively studied. In the current work, we focused on preparation of biocomposites based on polypropylene and Vietnamese rice husk flour having narrow size distribution (100–125 μm) with the presence of maleic anhydride grafted polypropylene as a compatibilizer. The effect of rice husk flour and maleic anhydride grafted polypropylene content on properties of composites was investigated. The results showed that mechanical parameters as well as thermal stability were significantly improved at relatively high rice husk content by the addition of maleic anhydride grafted polypropylene.